Global Injustice and Redistributive Wars - Kasper Lippert-Rasmussen (Law, Ethics and Philosophy, 2015)
On Pogge’s view, we —people living in rich countries— do not just allow the global poor to die. Rather, we interfere with them in such a way that we make them die on a massive scale. If we did the same through military aggression against them, surely, it would be permissible for these people to wage war on us to prevent this. Suppose Pogge’s analysis of the causes of global poverty is correct, and assume the moral permissibility of self-defence by poor people in the hypothetical military action scenario just mentioned. If these assumptions are correct, poor countries could start just and, even possibly, morally permissible redistributive wars against us provided various additional conditions are met. To avoid misunderstanding, I should stress that my main claim is the conditional equivalence claim, namely that if Pogge’s analysis of the causes of global poverty is correct, our relation to poor countries is morally equivalent to one in which we each year killed many of the global poor by military means. I do not claim (i) that Pogge’s analysis is correct; (ii) that, as a matter of fact, it is morally permissible for poor countries to wage redistributive wars against rich countries; (iii) that it is not the case that anything that is impermissible for poor countries to do in the latter situation involving military aggression —e. g. deliberately targeting rich civilians— is impermissible in redistributive wars as well.